CHARACTER BUILDING PADA MANUSIA (Analisis Terhadap Budaya Suku Dayak Losarang Indramayu) - Tarsono Tarsono (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2014)
Humans are unique creatures because they have a different character each other. The character is a strong trait of a man that its formation is influenced by their culture. The tribe of Dayak Losarang in Indramayu district is one of unique custom that located in urban area. Their uniqueness is including how to dress, how to communicate, how to worship and make sense of life. Push factors and pull factors that make them survive in indigenous communities are some rituals which are: a) kungkum, b) pepe, c) ngaula ning anak rabbi, d) ruatan putri keraton, e) pemurnian diri (self-purification), and f) Kliwon Friday night.